Combined T4 + T3 therapy versus T4 monotherapy effect on psychological health in hypothyroidism: A systematic review and meta‐analysis. (27th April 2022) - Lan, Huiyu; Wen, Junping; Mao, Yaqian; Huang, Huibin; Chen, Gang; Lin, Wei
Abstract: Purpose: To evaluate whether T4 + T3 combination therapy had advantages in improving psychological health compared with T4 monotherapy. Methods: We searched PubMed, Embase, Cochrane Library, and Web of Science from January 2000 to March 2021, and updated in September 2021. The inclusion criteria (prospective study, published in English, had a T4 + T3 combination therapy test group and a T4 monotherapy control group, patients aged ≥18 years and with overt primary hypothyroidism, and published after January 2000) were applied by two reviewers; any disagreement was resolved by a third reviewer. The two reviewers independently extracted data using a standard data form and assessed the risk of bias using the Cochrane risk of bias tool. Coprimary outcomes included the psychological health measures of depression, fatigue, pain, anxiety and anger, measured using validated and reliable instruments. Results: Eighteen of 2029 studies (883 patients) were included in the meta‐analysis. No significant difference was found between T4 + T3 combination therapy and T4 monotherapy with regard to depression (standardized mean difference [SMD]: −0.06, 95% confidence interval [CI]: −0.18; 0.07), fatigue (SMD: 0.06, 95% CI: −0.13; 0.26), pain (SMD: −0.01, 95% CI: −0.24; 0.22), anxiety (SMD: 0.01, 95% CI: −0.15; 0.17) and anger (SMD: 0.05, 95% CI: −0.15; 0.24). Methodological heterogeneity had no influence on the results. The patients preferred combination therapy significantly. Conclusions: Compared with T4 monotherapy, T4 + T3 combination therapy had no significant advantage in improving psychological health. For patients who are unsatisfied with LT4 monotherapy, the patient and the physician should make a joint decision concerning therapy.